(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study seeks to assess the effectiveness of zakat in supporting sustainable development in Burkina Faso, within a research framework that combines Islamic economic analysis with an applied approach to social finance. The study is grounded in the hypothesis that zakat—despite its widespread presence in African Muslim societies—is still often perceived primarily as an individual financial obligation, discharged directly to eligible beneficiaries, without sufficient recognition of its profound economic and developmental functions. Consequently, it has not been adequately activated as an instrument of Islamic fiscal policy capable of generating a structural impact on the economy and society. Adopting an analytical and evaluative methodology, the study examines the economic dimensions of zakat and its role in stimulating the productive cycle, redistributing income and wealth, reducing poverty and social vulnerability, and potentially enhancing economic stability by mitigating fluctuations associated with financial imbalances. Furthermore, the study offers an applied reading of the Burkinabè context, highlighting the significant potential for activating zakat within an institutional framework capable of ensuring systematic collection, sound management of its designated channels of expenditure, and the effective allocation of resources toward development projects with sustainable returns. The study concludes that zakat constitutes an integrated socio-economic system that transcends the boundaries of a purely financial act of worship, evolving into a strategic tool for achieving sustainable development when supported by appropriate legislative and institutional structures. Accordingly, it recommends strengthening awareness of the higher objectives (maqāṣid) of zakat and developing practical models for its implementation in Burkina Faso, in a manner that enhances its role in supporting economic and social development and contributes to the advancement of socially oriented fiscal policies.